Refrigeration and air-conditioning - Trott, A. R. (Albert Runcorn), 1919-; Welch, T. (Oxford ; Boston, Mass. : Butterworth Heinemann, 2000)
The use of refrigeration, either directly or as part of an air-conditioning system, is essential to almost every branch of industry. There is a need for practitioners to familiarise themselves with the general principles and methods of refrigeration and air conditioning, and the types of plant and operation currently in use. This book provides a comprehensive introduction to the principles and practice of refrigeration and air-conditioning for the uninitiated student and a general overview of the industry for the practitioner. The fundamentals of the subject are introduced without involving th.
Fundamentals -- The refrigeration cycle -- Refrigerants -- Compressors -- Oil in refrigerant circuits -- Condensers and water towers -- Evaporators -- Expansion valves -- Controls and other circuit components -- Selection and balancing of components -- Materials. Construction. Site erection -- Liquid chillers. Ice. Brines. Thermal storage -- Packaged units -- Refrigeration of foods. Cold storage practice -- Cold store construction -- Refrigeration in the food trades -- meats and fish -- Refrigeration for the dairy, brewing and soft drinks industries -- Refrigeration for fruit, vegetables and other foods -- Food freezing. Freeze-drying -- Refrigerated transport, handling and distribution -- Refrigeration load estimation -- Industrial uses of refrigeration -- Air and water vapour mixtures -- Air treatment cycles -- Practical air treatment cycles -- Air-conditioning load estimation -- Air movement -- Air-conditioning methods -- Dehumidifiers and air drying -- Heat pumps. Heat recovery -- Control systems -- Commissioning -- Operation. Maintenance. Service. Fault-finding. Training -- Efficiency and economy in operation -- Catalogue selection.
Includes bibliographical references (p. [369]-372) and index.
Keywords: Refrigeration and refrigerating machinery; Air conditioning; Electronic books